An Investigation into Stylistic Devices in "The Thorn Birds" by Colleen Mccullough and their Vietnamese translational equivalents - Phan Thi Kim Dung
Chapter 1.Introduction; Chapter 2. Literature review and theoretical background; Chapter 3 Research methodology; ...